HEALTH CHALLENGES OF FEMALE HAWKERS IN LAFIA METROPOLIS: AN EXPLORATORY STUDY OF FEMALE YAM HAWKERS - Idyorough, A.E.; Ishor, D.G. (European Scientific Journal, ESJ, 2014)
This study examined health challenges of female yam hawkers in Lafia metropolis, central Nigeria. The objectives of the study were to identify female yam hawkers in Lafia metropolis, to determine the hazards, health and otherwise faced by the hawkers as well as to identify strategies for their social cum economic empowerment. Accidental sampling technique was used to select thirty-four female yam hawkers from unknown universe of Lafia metropolis on whom structured questionnaires were administered. Empirical data was analysed using Epi-Info software. Findings revealed that female yam hawkers in Lafia metropolis who, are in their economically active years and majorly none-literate encounter serious health challenges including body pain, fatigue, fever, accidents and isolated cases of sexual assault. It was recommended, among other things therefore, that female yam hawkers in Lafia should form a cooperative so that they can access loans or aids from financial institutions, government or non-governmental organizations to expand their business in order to enable remain in a particular location in order to avoid or reduce the health challenges they do experience during hawking.